2006
DOI: 10.1103/physrevb.74.035205
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of arsenic clustering in silicon

Abstract: A model of arsenic clustering in silicon is proposed and analyzed. The main feature of the proposed model is the assumption that negatively charged arsenic complexes play a dominant role in the clustering process. To confirm this assumption, electron density and concentration of impurity atoms incorporated into the clusters are calculated as functions of the total arsenic concentration. A number of the negatively charged clusters incorporating a point defect and one or more arsenic atoms are investigated. It i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
0
12
2
2
Order By: Relevance
“…Various arsenic‐vacancy clusters as well as SiAs aggregates or precipitates were observed that contribute to the deactivation of arsenic. Even now, they are subjects of numerous experimental studies and first‐principles calculations 14–18. In spite of the large amount of scientific literature, the SiAs system is still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Various arsenic‐vacancy clusters as well as SiAs aggregates or precipitates were observed that contribute to the deactivation of arsenic. Even now, they are subjects of numerous experimental studies and first‐principles calculations 14–18. In spite of the large amount of scientific literature, the SiAs system is still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Как показано в работах [4,16,17], диффузионный поток примеси можно представить в виде (2) Здесь χ -общая концентрация носителей заряда, нормированная к собственной концентрации носи-телей n e : (3) Из закона сохранения частиц и условий (2) и (3) получаем следующее нелинейное уравнение диффузии:…”
Section: модель диффузии примесей в кремнииunclassified
“…Приведен-ные методы и результаты иссле-дований основаны на более ранних публикациях [4][5][6][7][8][9][10][11].…”
Section: Introductionunclassified
“…[4], to describe the impurity clustering during transient enhanced diffusion of As and P, one can use the expression…”
Section: Equation Of Vacancy Diffusion [11]mentioning
confidence: 99%
“…[1,2] provide some evidence of disagreement with the experimental data in the vicinity of the interface. The difference is mainly due to the use of inadequate clustering models for the description of high concentration diffusion [4], due to the influence of interfaces on the defect distributions [5], due to dopant atom trapping by immobile sinks [6], and due to the influence of stresses on the dopant and defect diffusion [7,8]. The principal goal of this investigation is to obtain a set of equations describing impurity diffusion and quasichemical reactions of dopant atoms and point defects near the surface or interface to simulate adequately the transient enhanced diffusion in shallow implanted layers.…”
Section: Introductionmentioning
confidence: 99%